SPECIFIC FEATURES OF THE SPREAD OF CERTAIN DISEASES IN SURKHANDARYA REGION (International Conference on Education, Psychology and Humanities, 2026)
This thesis analyzes the geographic characteristics of certain diseases prevalent in Surkhandarya region, their dynamics, and their association with socio-ecological factors. The relationship between the region's climatic conditions, soil structure, water supply, and living standards of the population and the spread of diseases has been examined. The research findings are of practical importance for improving the healthcare system and developing preventive measures.
Keywords: Surkhandarya region, medical geography, disease spread, climatic factors, ecology, demography, epidemiology.